An Ordinance Defining Offenses and Providing Punishments for the Same, in DELPHOS CARRIER, Aug. 1, 1884, at 2 - (:unkn) unknown (My University, 1884)
§ 19: Any person who shall within the city of Delphos, carry about his or her persons any concealed pistol, dirk, bowie knife, revolver, slung shot, billy, false knuckles or any other deadly weapons, shall be fined in any sum not exceeding fifty dollars. Provided that upon application to the mayor by any person he may grant a permit to carry a pistol...
Keywords: CARRY